2D Octagon-Structure Carbon and Its Polarization Resolved Raman Spectra - He, Chunshan (Nanomaterials (Basel), 2020)
We predict a new phase of two-dimensional carbon with density functional theory (DFT). It was found to be semimetal with two Dirac points. The vibrational properties and the polarization resolved Raman spectra of the carbon monolayer are predicted. There are five Raman active modes: 574 cm(−1) (E(g)), 1112 cm(−1) (B(1g)), 1186 cm(−1) (B(2g)), 1605 cm(−1) (B(2g)) and 1734 cm(−1) (A(1g)). We consider the incident light wave vector to be perpendicular and parallel to the plane of the carbon monolayer. By calculating Raman tensor of each Raman active mode, we obtained polarization angle dependent Raman intensities. Our results will help materials scientists to identify the existence and orientation of octagon-structure carbon monolayer when they are growing it.